PENGGUNAAN PROBIOTIK PADA PAKAN IKAN BAWAL BINTANG (Trachinotus blochii). - Hamdani Hamdani; Saptono Waspodo; Ayu Adhita Damayanti (Jurnal Perikanan Unram, 2018)
The research aimed to analyze the effect of adding different dose of probiotics on the growth of star pomfret fish (Trachinotus blochii). This research was conducted for 30 days from January 29 th to March 2 nd 2018, at Balai Perikanan Budidaya Laut (BPBL) Lombok, West Nusa Tenggara Province. The design used in this study were Complete Random Design (CRD) consisting of 4 treatments and 4 replications, namely: P1 administration of probiotics 25 ml / kg of feed as control, P2 administration of probiotics 30 ml / kg of feed, P3 administration of probiotics 35 ml / kg feed, and P4 giving probiotics 40 ml / kg of feed. The data obtained were analyzed using analysis of variance (ANOVA) at a real level of 5% using the SPSS program and Tukey's advanced test was carried out with a 5% significance level to find out the best treatment. The parameters observed were absolute weight growth, absolute length, survival rate and water quality. The results showed that the effect of addition of probiotics significantly effected to the growth and survival of star pomfret seeds (Trachinotus blochii). The probiotics supplementation of 40 ml / kg feed gave best growth of star pomfret seeds (Trachinotus blochii)